Study on carbapenemase-producing bacteria by matrix-assisted laser desorption/ionization approach. - Michał Złoch; Paweł Pomastowski; Markus Peer; Katrin Sparbier; Markus Kostrzewa; Bogusław Buszewski (PLoS ONE)
The development of new techniques for the detection of carbapenemase activity is of great importance since the increased incident of resistance against carbapenems represents a serious threat to global public health. In this context, the matrix-assisted laser desorption/ionization approach already demonstrated to be a reliable tool for rapid carbapenemase detection. As a newly developed test, there is still a lack of in-depth analysis of its robustness and possible wider application. The main goal of this study was to evaluate the potential for using the design MBT STAR-Carba assay as the pre-characterization method for Enterobacterales and P. aeruginosa strains in terms of the produced classes of carbapenemases using modified procedure parameters-various suspension densities and incubation times. Moreover, its usefulness for the in-depth analysis and characterization of metallo-β-lactamases (MBL) was tested by applying inhibition assays. In this study, the designed assay proved to be a sensitive tool for the detection of carbapenemase hydrolytic activity, which can be successfully used to partially classify the class of carbapenemase present. Additionally, the use of defined high concentration suspensions would allow to shorten the incubation time to 1 minute for certain strains. Considering that the assay was also suitable to investigate the effect of different inhibitors on the MBL activity, it demonstrates far higher discriminatory potential than only a rapid routine carbapenemase detection tool and could be used as a susceptibility assay.